1985
DOI: 10.1111/j.1471-0528.1985.tb01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal studies in women with premenstrual tension

Abstract: Summary. Serum hormone concentrations were determined at intervals during the last 17 days of the menstrual cycle in 35 patients with premenstrual tension (PMT) and 11 control subjects without symptoms. The maximum mean concentration of oestradiol occurred 17 days before menstruation in the patients and 14 days before in the controls. The maximum concentrations of progesterone were similar in the two groups but the mean concentrations rose carlier in the cycle in the patients with PMT. These results suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Myriad investigations of estrogen, progesterone, testosterone, LH, FSH, cortisol and prolactin concentrations have not demonstrated a consistent pattern of hormonal excess or deficiency in women with PMS/PMDD (Watts et al, 1985;Rubinow et al, 1988). Recent hypotheses advanced to explain the relationship between ovulation and PMS include:…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Myriad investigations of estrogen, progesterone, testosterone, LH, FSH, cortisol and prolactin concentrations have not demonstrated a consistent pattern of hormonal excess or deficiency in women with PMS/PMDD (Watts et al, 1985;Rubinow et al, 1988). Recent hypotheses advanced to explain the relationship between ovulation and PMS include:…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, PMS shares some general clinical features with the GABA mediated anxiety disorders such as comorbidity with panic disorder; panic type response to stressors like lactate infusion or carbon dioxide inhalation and moderate clinical improvement with alprazolam therapy (Facchinetti et al, 1998). However, studies measuring progesterone concentrations across the menstrual cycle have not revealed altered progesterone levels in women with PMS (Rubinow et al, 1988;Watts, 1985;Hammarback et al, 1989) and almost uniformly, progesterone therapy is not more effective than placebo for the treatment of PMS Freeman et al, 1990).…”
Section: Progesterone Progesterone Metabolites and Pmsmentioning
confidence: 95%
“…7 Hormonal fluctuation like increase level of estradiol and progesterone during premenstrual phase also responsible for premenstrual changes. 8 Interaction of CNS neurotransmitters & sex hormones leads to premenstrual stress which shifts ANS toward sympathetic. Most evidences suggest that there is decrease in serotonin and beta-endorphin level during premenstrual phase.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The gonadal hormones fluctuation during the menstrual cycle is associated with significant changes in multiple neurohumoral homeostatic mechanisms of the body. [13] Estrogen increases sympathetic baroreflex sensitivity and also has a prolonged stimulatory action on CRH gene promoter and central non-adrenergic system which indicate changes in sympathetic activity responses significantly more during premenstrual late luteal phase (LL) phase than post-menstrual early follicular phase. [14,15] Kale and Kathole [4] observed that increased activity of sympathetic system during pre-menstrual phase is due to pre-menstrual stress.…”
Section: Discussionmentioning
confidence: 99%